Error Detection–Based Model to Assess Educational Outcomes in Crisis Resource Management Training: A Pilot Study. (25th April 2017) - Bouhabel, Sarah; Kay‐Rivest, Emily; Nhan, Carol; Bank, Ilana; Nugus, Peter; Fisher, Rachel; Nguyen, Lily HP
Abstract : Otolaryngology–head and neck surgery (OTL‐HNS) residents face a variety of difficult, high‐stress situations, which may occur early in their training. Since these events occur infrequently, simulation‐based learning has become an important part of residents' training and is already well established in fields such as anesthesia and emergency medicine. In the domain of OTL‐HNS, it is gradually gaining in popularity. Crisis Resource Management (CRM), a program adapted from the aviation industry, aims to improve outcomes of crisis situations by attempting to mitigate human errors. Some examples of CRM principles include cultivating situational awareness; promoting proper use of available resources; and improving rapid decision making, particularly in high‐acuity, low‐frequency clinical situations. Our pilot project sought to integrate CRM principles into an airway simulation course for OTL‐HNS residents, but most important, it evaluated whether learning objectives were met, through use of a novel error identification model.